Prevalence and predictors of pornography exposure during the third wave of the COVID-19 pandemic: A web-based cross-sectional study on students in Bangladesh - Hossain, Md. Tanvir; Ahammed, Benojir; Jahan, Nusrat; Islam, Md. Akhtarul; Rahman, Md. Mostafizur; Khan, Bayezid; Sarker, Md. Juwel Ahmed; Nibir, Md. Mahdi-Al-Muhtasim; Hasan, Mahamudul; Hasib, Mir; Rahman, Rumana; Islam, Md. Nazrul (Frontiers in Public Health, 2022)
Background Pornography exposure, particularly among students, in Bangladesh, has increased in the twenty-first century. However, pornography exposure during the COVID-19 pandemic, when people were compelled to “stay at home” and relied extensively on the internet for all forms of activities, including academia, socializing, and communication, has remained unexplored. The present study aimed to assess the prevalence of pornography exposure among students during the third wave of the COVID-19 pandemic and to determine the associated predictors. Methods A web-based cross-sectional study was carried out among students with certain specifications, i.e., current students at high school/college/university with access to the internet and valid social media accounts. By administering a semi-structured e-questionnaire using Google Forms, a total of 646 valid responses were retained for this study. The data were analyzed in two phases by Pearson's Chi-square and multiple logistic regression model, using IBM SPSS Statistics, version 25. The results were expressed as an adjusted odds ratio (AOR) with a 95% confidence interval (95% CI). Results The findings suggest that 75.9% of students were exposed to pornography during the third wave of the COVID-19 pandemic and preferred to watch the amateur/professional genre of pornography. Pornography exposure was significantly associated with age and relationship status, as students aged 22–24 years (95% CI: 1.01–2.41; p = 0.045) and over 25 years (95% CI: 1.61–10.03; p = 0.003) were more likely to watch pornography, while married students and those in relationships (95% CI: 1.24–3.49; p = 0.006) also watched pornography during the pandemic. In contrast, students who were living alone (95% CI: 0.38–0.92; p = 0.021), were living in the Khulna division (95% CI: 0.16–0.52; p < 0.001) or had a negative attitude toward pornography (95% CI: 0.94–0.99; p = 0.002) were less likely to be exposed to pornography. Conclusion Pornography exposure was higher among students in Bangladesh during the COVID-19 pandemic, and religiosity and disapproving attitudes toward pornography negatively influenced the pornography exposure. For a better understanding of the complex dynamics of socio-demographic issues with pornography exposure among students, extensive research is required for policymakers to devise appropriate strategies and interventions to ensure healthy and safe sex life for the younger population.